Use of business efficiency control system in strategic and operational activities of enterprises - Кушлик, О. Ю.; Ріщук, Л. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Grounded problem of the transition from strategy formulation development on a verbal level to specific numerical performance. The models of business performance management system (Performance Pyramid, Effective Progress and Performance Mesurement, Accountability Scorecard, Balanced Scorecard). Investigated the relationship between indicators of system models performance management and business approaches to their construction. Grounded of the key positions of using system business performance in strategic and operational activities of the company in conditions of development of market relations.